23. ANALISIS PENGGUNAAN OFFENSIVE CYBER OPERATIONS MENGHADAPI ANCAMAN NUKLIR IRAN - Ary Melysa; Ika Riswanti Putranti; Andi Akhmad Basith Dir (Journal of International Relations Diponegoro, 2016)
Iran's nuclear program was first initiated by joining the U.S. Atoms For Peace program. Ithowever, changed when Iranian Revolution was occuring in 1979. Since then, the U.S haswithdrawn its support to Iran's nuclear program. Although the program has beensuspended, Iran continues its development after war with Iraq. The U.S. concerned thatIran's new nuclear program was built to produce nuclear weapons. After failing to preventIran from developing its nuclear program through diplomatic approaches, the U.S. wasseeking a new alternative by using Offensive Cyber Operation or also known as OlympicGames. Together with Israel, the U.S. created the first ever cyber weapon called Stuxnet.The target of this operation is Uranium Enrichment Facility in Natanz, Iran. Specifically,Stuxnet has damaged around 1000 centrifuges whose primarily function is to enrich theuranium. This research aims to find out the reason of the U.S. in using Offensive CyberOperations instead of Conventional Military Operations with regard to Iran's nuclear threat.To do so, this research uses Offensive Realism theory with qualitative method. Theoutcome of this research is: the U.S. as a rational actor has chosen Offensive CyberOperations because the operation has brought the U.S. a number of strategic gains thatcannot be necessarily achieved by Conventional Military Operations. These strategic gainsare 1) Anonimity 2) Practicality in terms of distance, cost and risk 3) Execution easinessand 4) Political and bureaucracy leeway.